2004
DOI: 10.1007/s00442-003-1434-x
|View full text |Cite
|
Sign up to set email alerts
|

Persistent maternal identity effects on life history traits in Daphnia

Abstract: The aim of the present study was to examine the magnitude and persistence of maternal effects in Daphnia, in particular maternal identity effects. I studied life history traits of a single clone of Daphnia galeata born to 40 different mothers belonging to three age groups. Maternal identity had large effects on offspring traits, that is, identically treated clonal females differed substantially in respect to the traits of their offspring, including size at birth, age at maturity, and number of second generatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 31 publications
2
39
0
Order By: Relevance
“…Other studies have shown similar relationships where the effort per offspring (in terms of size or mass of eggs or neonates) increased with maternal body size for different clones of D. magna, under high and low food conditions (Glazier, 1992;Ebert, 1993;McKee and Ebert, 1996). Positive effects of maternal body size on OS were observed in other Daphnia species such as D. galeata (Sakwinska, 2004) or D. hyalina (Burns, 1995) and in other organisms (Bernardo, 1996) as well.…”
Section: Os Dependence On Maternal Body Sizesupporting
confidence: 54%
See 2 more Smart Citations
“…Other studies have shown similar relationships where the effort per offspring (in terms of size or mass of eggs or neonates) increased with maternal body size for different clones of D. magna, under high and low food conditions (Glazier, 1992;Ebert, 1993;McKee and Ebert, 1996). Positive effects of maternal body size on OS were observed in other Daphnia species such as D. galeata (Sakwinska, 2004) or D. hyalina (Burns, 1995) and in other organisms (Bernardo, 1996) as well.…”
Section: Os Dependence On Maternal Body Sizesupporting
confidence: 54%
“…Our results support the findings of Ebert (1993), showing that age and brood number did not affect OS in two D. magna populations from different artificial ponds, but the food level, maternal body size and brood size strongly affected OS. However, opposite results were observed for D. galeata (Sakwinska, 2004) where the juvenile growth increment differed between young, intermediate and older mothers, leading to a dependence of OS on maternal age. The observed variability in the factors determining OS in Daphnia could be attributed to interspecies differences.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…Although size at birth is an important fitness determinant (Tessier and Consolatti 1989;Lampert 1993), maternal effects on subsequent life stages should be considered when offspring performance and population dynamics are analyzed since offspring quality is not necessarily reflected in size at birth (Sakwinska 2004). Therefore, we reared first-clutch neonates of experimental mothers grown with the various food regimes on a 100% Syn diet.…”
Section: Discussionmentioning
confidence: 99%
“…The quality of the maternal environment influences traits such as size at birth and number of offspring (Sakwinska, 2004), strain-specific immunity to bacterial parasites (Little et al, 2003) and energy allocation to offspring (LaMontagne and McCauley, 2001). Interestingly, mothers reproducing in poor environments produced offspring more than twice as resistant to bacterial infection as mothers in favorable environments (Mitchell and Read, 2005).…”
Section: Bd Eads Et Almentioning
confidence: 99%